Primary MALT Lymphoma of the Breast Treated with Definitive Radiation. (10th May 2016) - Hissourou III, Mohammad; Zia, Sayyad Yaseen; Alqatari, Mahfood; Strauchen, James; Bakst, Richard L.
Abstract : We are reporting a case of a 59-year-old woman, with a family history of breast cancer, who presented with extranodal marginal zone lymphoma (MALT) of the left breast. She received definitive radiation therapy and remains without evidence of disease. Here, we present a case and review the current literature to determine the optimal treatment of this rare presentation of MALT.